Does Board Size Really Matter? Evidence from Australia - Setia-Atmaja, Lukas Y. (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This study examines the impact of board size of Australian firms on Tobinâs Q. Agency theory suggests that there is an inverse relationship between board size and Tobinâs Q (Yermack 1996; Eisenberg et al. 1998). The resource dependence argument, however, hypothesizes that larger boards can lead to higher performance as the CEOâs need for advice is a function of the complexity of the organization (Pfeffer 1972; Klein 1998). Analyzing a panel data of 1,530 firm-year observations using random effects technique, this study finds a positive relationship between board size and Tobinâs Q. The random effects regression results also reveal that the positive relationship between board size and Tobinâs Q is driven by firm size as this positive relationship is only found in larger firm sample but not in the smaller firm sample. The overall results support the resource dependence argument.